Topographic complexity drives trait composition as well as functional and phylogenetic diversity of understory plant communities in microrefugia: New insights for conservation - Kata Frei; Anna E-Vojtkó; Csaba Tölgyesi; András Vojtkó; Tünde Farkas; László Erdős; Gábor Li; Ádám Lőrincz; Zoltán Bátori (Forest Ecosystems)
Topographic complexity supports the maintenance of a high diversity of microhabitats, which may act as important ‘safe havens’ – or microrefugia – for biodiversity. Microrefugia are sites with specific environmental conditions that facilitate the persistence of species during environmental changes and exhibit unique eco-evolutionary dynamics. However, our knowledge about how topographic complexity and related eco-evolutionary selective forces influence the functional and phylogenetic signatures of species assemblages in microrefugia is very limited. Although the conceptual framework on the systematic integration of plant functional traits into the study of refugia is well established, more empirical studies on functional trait composition and functional diversity in refugia are urgently needed for more effective conservation. Here we analyzed the distribution of various plant functional traits and phylogenetic patterns in microhabitats (south- and north-facing slopes, and bottoms) of 30 large topographic depressions (i.e. doline microrefugia) and microhabitats of the surrounding plateaus in two distant forested karst regions. We found that plant assemblages in the understory of dolines and their surroundings are characterized by unique functional values and combinations of traits. Doline bottoms had the highest functional diversity among doline microhabitats and supported plant assemblages with considerably different trait compositions from the plateaus. Bottoms also had the highest phylogenetic diversity. These results suggest that topographic complexity in forested dolines has a significant effect on the distribution of plant functional traits in the understory. High functional and phylogenetic diversity in doline bottoms can have important consequences for the long-term survival of plant populations, highlighting that these microhabitats may provide a higher resilience and support an adaptive community-level response to natural and anthropogenic stressors. Understanding mechanisms that drive the survival of species within microrefugia is required to determine the best conservation and management strategies.